INOVASI KURIKULUM DAN PENGUATAN KARAKTER DALAM PEMBELAJARAN BIOLOGI (STUDI KASUS DI SMAS ISLAMIC VILLAGE TANGERANG) - Naifah, Amalia Maharani; Sifa, Khoironi; Maida, Citra; Juliasari, Devita; Khoirunnisa, Aida; Usman, Usman (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
The challenges of 21st-century education require high school graduates to not only excel academically, but also to have strong characters such as critical thinkers and global insight. However, biology learning often still focuses on the transfer of theoretical knowledge and does not optimize the potential for strengthening character. This gap underlies the importance of research on innovative curriculum models. Therefore, this study aims to determine how the implementation of an innovative curriculum can strengthen students' character in biology learning. This study uses a qualitative descriptive method with in-depth interview techniques to collect primary data. The key informant was the head of the curriculum division at a private high school in Tangerang. The results showed that the school innovatively integrated the National Curriculum with the International Baccalaureate (IB) framework. In the context of biology, this hybrid model encourages students to become active learners through independent investigation and analysis of global case studies, which directly fosters inquisitive, reflective, and open characters to world perspectives. It is concluded that the combination of the National and IB curricula is an effective strategy to transform biology learning from merely transferring knowledge to a means of strengthening essential characters that are relevant to global demands. ABSTRAKTantangan pendidikan abad ke-21 menuntut lulusan sekolah menengah atas tidak hanya unggul secara akademis, tetapi juga memiliki karakter kuat seperti pemikir kritis dan berwawasan global. Namun, pembelajaran biologi sering kali masih berfokus pada transfer pengetahuan teoretis dan kurang mengoptimalkan potensi penguatan karakter. Kesenjangan ini melatarbelakangi pentingnya penelitian mengenai model kurikulum yang inovatif. Oleh karena itu, penelitian ini bertujuan untuk mengetahui bagaimana implementasi kurikulum inovatif dapat memperkuat karakter siswa dalam pembelajaran biologi. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik wawancara mendalam untuk mengumpulkan data primer. Narasumber kunci adalah kepala bidang kurikulum di salah satu sekolah menengah atas swasta di Tangerang. Hasil penelitian menunjukkan bahwa sekolah tersebut secara inovatif mengintegrasikan Kurikulum Nasional dengan kerangka International Baccalaureate (IB). Dalam konteks biologi, model hibrida ini mendorong siswa menjadi pembelajar aktif melalui investigasi mandiri dan analisis studi kasus global, yang secara langsung menumbuhkan karakter inkuisitif, reflektif, dan terbuka terhadap perspektif dunia. Disimpulkan bahwa kombinasi kurikulum Nasional dan IB merupakan strategi yang efektif untuk mentransformasi pembelajaran biologi dari sekadar transfer ilmu menjadi wahana penguatan karakter esensial yang relevan dengan tuntutan global.